Relationship Between Physical Changes and Anxiety Premenopause Women in Kalasey 1 Village - Lolowang, Roosye Marie (Interdisciplinary Social Studies, 2022)
The findings of a preliminary study on 10 premenopausal women revealed that 7 of them had irregular menstrual cycles, hot flushes (a feeling of heat in the face), night sweats, and mood changes like stress, irritability, and being easily surprised, which led to stress, heart palpitations, and disturbed sleep. This study aims to determine the relationship between physical changes and anxiety in premenopausal women in Kalasey 1 Village, Mandolang District, Minahasa Regency. This study used quantitative research methods. The research subjects used were premenopausal women in Kalasey 1 Village, Mandolang District, Minahasa Regency with a total of 66 people. The data analysis technique used in this study is the product moment correlation technique using manual calculations and computer assistance programs, namely SPSS.22. There is a positive and significant relationship between physical changes and anxiety in premenopausal women with an rxy correlation coefficient of 0.286, then the correlation coefficient test is carried out using the t-test and the resulting t-count = 2.387 and t-table = 1.668. Ho is rejected and Ha is accepted. So, it can be concluded that there is a significant relationship between physical changes and anxiety in premenopausal women.